Equitable Housing for All: Unlocking Social Inclusion in Port Harcourt, Rivers State (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
This paper aims to explore the critical issue of equitable housing for all, with a particular focus on promoting social inclusion and empowerment among low-income earners. As urbanization continues to accelerate, the disparities in access to adequate housing have become more pronounced, posing significant challenges to sustainable and inclusive development. Drawing upon recent trends and best practices, this article identifies innovative strategies and policy interventions that can pave the way for a fairer and more inclusive housing landscape. By emphasizing the importance of community engagement, supportive infrastructure, and government collaboration, this study proposes a comprehensive approach to ensure that housing becomes a catalyst for social cohesion and the upliftment of marginalized communities.